2023
DOI: 10.1186/s12870-023-04106-0
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Zeatin induce regulation the biosynthesis of 2-acetyl-1-pyrroline in fragrant rice (Oryza sativa L.) seedlings

Abstract: Background In plants, cytokinin is activated into trans-zeatin to fight abiotic stresses. However, the mechanism of the effect of trans-zeatin on 2-acetyl-1-pyrroline (2-AP) biosynthesis in fragrant rice has yet to be studied. The present study was conducted to explore the effects of exogenous trans-zeatin on enzymes activities, genes expression, and precursors involved in 2-AP biosynthesis and 2-AP contents as well as the seedling quality of a fragrant rice cultivar viz., Meixiangzhan2. Four c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…Although glutamic acid and proline are precursors of 2-AP, proline plays a more critical role in aroma synthesis [ 25 ]. Similar to the experimental results of spraying trans zeatin on fragrant rice seedlings, the glutamic acid content in fragrant rice seedlings decreased [ 26 ]. However, the content of proline and 2-AP significantly increased.…”
Section: Discussionsupporting
confidence: 73%
“…Although glutamic acid and proline are precursors of 2-AP, proline plays a more critical role in aroma synthesis [ 25 ]. Similar to the experimental results of spraying trans zeatin on fragrant rice seedlings, the glutamic acid content in fragrant rice seedlings decreased [ 26 ]. However, the content of proline and 2-AP significantly increased.…”
Section: Discussionsupporting
confidence: 73%
“…15,30,31 The results of our study showed that there existed a significant and negative relationship (correlation coefficient < −0.5) between 2-AP content and BADH2 expression, which also agreed with our previous findings. 7,32 On the other hand, the content of GABA, which could be formed by BADH2, decreased with increased temperature and showed a positive correlation (correlation coefficient > 0.5) with 2-AP content. This finding was inconsistent with the study by Bao et al 7 but agreed with the study by Mo et al 1 GABA content has been shown to respond to stresses, and our results were consistent with an earlier study which indicated temperature-induced regulation of GABA metabolism in plants.…”
Section: Discussionmentioning
confidence: 96%
“…The present performance in VIP scores (Figure 1d−g) agreed that 2-AP was recognized as the pivotal compound of aroma in fragrant rice, physiologically, being determined by the activities of ProDH, P5CS, OAT, the content of Pro, P5C, and MG. 1,30,37,38 The resultant Glu100 and Glu500 treatment increased the P5C, MG content, P5CS, ProDH, and OAT activities with similar trends of mRNA transcription levels for 2-AP accumulation (SI, Figure S3cd,f−k), which were coordinated with the studies of exogenous application on fragrant rice to improve the 2-AP. 4,39,40 It was inferred that exogenous Glu might up-regulate OAT, inducing the Glu and Pro catabolism and accumulation to resume 2-AP biosynthesis at As stress defense level (Figure 4, and SI, Figure S6).…”
Section: ■ Discussionmentioning
confidence: 99%